EVALUATION OF THE BASIC EDUCATION CURRICULUM: PREPARING A SUPERIOR GENERATION THROUGH A HOLISTIC APPROACH - Rusiadi Rusiadi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Evaluation of the basic education curriculum is crucial in the learning process to ensure that it prepares a superior generation. A holistic approach to evaluation requires a thorough understanding of the various aspects that influence learning, from academic competence to social skills to character values. This article explores curriculum evaluation methods that take these elements into account, and their impact on developing students' full potential. Through the analysis of quantitative and qualitative data from various primary schools, the study shows how the application of a holistic approach can provide a comprehensive picture of curriculum effectiveness and provide recommendations for continuous improvement.